Sex reversal and the androgenic gland (AG) in Macrobrachium rosenbergii: A review - Kianann Tan (Aquaculture and Fisheries, 2020)
The male giant freshwater prawn (Macrobrachium rosenbergii) generally exhibit faster growth rates compared to females of similar age. Consequently, the practice of culturing monosex (all-male) prawn can increase both the production yield and income. Manually selecting males for culture during the grow-out period has long been practiced in commercial prawn farming, but is labor-intensive and generally unsuccessful in producing a male monoculture. The androgenic gland (AG) is essential for sexual differentiation in prawn and development of male primary and secondary sexual characteristics. Microsurgical removal of the AG (andrectomy) from male prawn at an early development stage will transform the male into a fully-functioning neo-female. The M. rosenbergii androgenic gland-specific insulin-like hormone (Mr-IAG) plays critical roles in male spermatogenesis and male sexual development. RNA interference (RNAi) is a highly specific post-transcriptional interference or silencing of gene expression in cells. Silencing Mr-IAG had induced full and functional sex reversal of male to neo-female (genetic male with a female phenotype). Microsurgical removal of AG and RNAi are two different approaches to producing neo-females and both methods target the manipulation of AG for efficient sex-reversal. Neo-females can mate with normal males to produce all-male prawn progeny, which can be used for commercial prawn farming and to improve production efficiency and profitability. This article reviewed recent research related to the development and functions of AG and the testis and their interactions with morphological differentiation at various stages for male M. rosenbergii, aiming to increase understanding on this topic and facilitate discovery of new techniques for advancing M. rosenbergii aquaculture.